Analysis of the Impact of the 2019–20 Australian Bushfire Season on the Atmospheric Environment - Zhang, Jie; Sheng, Zheng; He, Yang; Zuo, Xinjie; Jin, Bo; He, Mingyuan (Frontiers in Earth Science, 2021)
The 2019–20 Australian bushfire produced strong plumes that carried massive quantities of gases and aerosols through the tropopause into the stratosphere. The 2019 El Niño and a rare sudden stratospheric warming (SSW) in the Southern Hemisphere (SH) that occurred in austral spring 2019 caused reduced precipitation in eastern Australia, which caused the strongest bushfire in history in terms of area and disaster degree. High-intensity bushfires triggered chemical reactions, including the rapid secondary formation of formic acid (FA). The strong intensity of the bushfire and the isolated environment allowed their impacts to be well detected. We identified the most active bushfire period (December 30–January 1) and its impacts on atmospheric components. The trajectory and lifetime of bushfire plumes were analysed to reveal the bushfire process and most active period. Based on multiple satellite and reanalysis products, unique variations in atmospheric components were identified and attributed to 3 main factors: bushfire development period, stratosphere heating mechanism and rapid secondary formation of FA. The bushfire gradually increased in intensity from June, reached its most active period from December 30–January 1, and then weakened. The bushfire development period caused delays in the plumes and peak values of gases (CO, SO2, FA and ozone) and temperature. The diurnal cycle, particle concentration and time restricted the total radiative forcing of aerosols and gases, which prevented a high rate of temperature increase similar to that of gas input from plumes. The strong intensity of the bushfire caused rapid secondary formation of FA, which caused a sharp increase in FA production from December 30–January 1.